Differentiate 6x^2+2x+1 by first principles, showing every step in the process.

f(x) = 6x2+2x+1, f'(x)= [f(x+h)-f(x)]/h here is the original equation and the formula used to differentiate from first principles. For this proof the limit of h is: h=0 and should be stated throughout, but is not due to formatting problems.f'(x)=[6(x+h)2+2(x+h)+1 - (6x2+2x+1)]/h = [6(x2+2xh+h2)+2x+2h+1-6x2-2x-1]/h = [6x2+12xh+6h2+2x+2h+1-6x2-2x-1]/h here the formula are combined and brackets expanded.f'(x) =[12xh+6h2+2h]/h = 12x+6h+2, h=0 therefore 12x+6h+2= 12x+2, therefore f'(x) = 12x+2 the negatives from the previous line are resolved and the equation is canceled down to the answer.

Answered by Thomas N. Maths tutor

5291 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Find the gradient of the curve y = 5(x^2} - 2x + 3 when x = 4


Differentiate with respect to x, y = (x^3)*ln(2x)


Solve the differential equation: dy/dx = tan^3(x)sec^2(x)


How would you differentiate f(x)=3x(2x-1)^2


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences